A Arquitetura Metodológica de Michael Faraday - Reis, João Batista Alves dos (2006)
The present research aimed to show the construction of Michael Faraday s (1791- 1867) electromagnetic theory, from an architectural methodological perspective. Thus, the starting point were the supporting pillars: the notion of the unity of the forces of nature and the goal of improving the mind. Next, it was sought to identify the constitutive elements, the dialogue between which would result in a harmonious building: observation, experiment and mental images, which would lead to the studies on the relationship between electromagnetism and light. Finally, Faraday s activity in the divulgation of science was approached, which showed a coherence with his lifelong principles. The main source for analysis was Faraday s diary, Faraday s Diary: Being the Various Philosophical Notes of Experimental Investigation. Other sources included Experimental Researches in Electricity and personal letters